2018
DOI: 10.1080/10599231.2018.1490595
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration and the Emerging Craft Brewing Industry: An Exploratory Study

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Development of hybrid logics and collaborative business models in the Irish craft beer sector was investigated by Drakopoulou et al (2018) from an entrepreneurial perspective. Micro and small-sized craft breweries in Australia were investigated by Alonso et al (2018) who found that horizontal collaboration within other brewers helped increase product quality, gain basic knowledge of new recipes, and enhance strategic knowledge about the industry.…”
Section: Horizontal Collaboration In Small and Medium Firmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Development of hybrid logics and collaborative business models in the Irish craft beer sector was investigated by Drakopoulou et al (2018) from an entrepreneurial perspective. Micro and small-sized craft breweries in Australia were investigated by Alonso et al (2018) who found that horizontal collaboration within other brewers helped increase product quality, gain basic knowledge of new recipes, and enhance strategic knowledge about the industry.…”
Section: Horizontal Collaboration In Small and Medium Firmsmentioning
confidence: 99%
“…This research contributes and extends the research on horizontal collaboration by providing an in-depth insight into how horizontal collaboration occurs and how it is facilitated in micro and small enterprises within the drink industry. small firms in the drink sector by adding new themes of relational rent as a result of horizontal collaboration in micro and small breweries, including joint wholesale, visibility of the national brand, and joint export, to previously existing themes of process technology development, inbound logistics, marketing (Flanagan et al, 2017), knowledge sharing and new product development (Alonso et al, 2018;Drakopoulou Dodd et al, 2018).…”
Section: Academic Research Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Leon-Bravo et al (2017) studied collaboration in food supply chains to promote sustainability and suggest that companies should prioritize to collaborate with key actors responsible for ensuring product quality and safety. Alonso, O'Brien, and Alexander (2018) studied microand small-sized craft breweries and found that horizontal collaboration within other brewers helped increase product quality, gain basic knowledge of new recipes, and enhance strategic knowledge about the industry.…”
Section: Supply Chain Collaboration and Sme Performancementioning
confidence: 99%
“…Supply chain collaboration and integration are well-established practices to reduce uncertainties, and to streamline production and distribution systems (Leuschner, Rogers, and Charvet 2013;Ataseven and Nair 2017). Agri-SMEs can benefit from supply chain collaboration including horizontal collaborations (Alonso, O'Brien, and Alexander 2018) to improve product quality and safety (Leon-Bravo et al 2017), yet, success is not always guaranteed (Kottila and Ronni 2008;Dania, Xing, and Amer 2018). A better coordination of supply chains via collaboration would result in reduced food loss and, thus, increased firm performance; yet, current supply chains suffer from a high percentage of food waste (Devin and Richards 2018) and frequent food quality and sustainability issues (Bourlakis, Vlachos, and Zeimpekis 2011).…”
Section: Introductionmentioning
confidence: 99%